Efficient micro-mobility using intra-domain multicast-based mechanisms (M&M). - Helmy, Ahmed (Computer communication review.)
One very important metric in evaluation of IP mobility protocols is handover performance. Handover occurs when a mobile node changes its network point-of-attachment. If not performed efficiently, handover delays, jitters and packet loss directly impact applications and services. With the Internet growth and heterogeneity, it becomes crucial to design efficient handover protocols that are scalable, robust and incrementally deployable. Mobile IP (MIP) has been shown to exhibit poor handover performance during micro-mobility. We propose a new architecture for providing efficient and smooth handover, while being able to coexist and inter-operate with other technologies. Specifically, we propose an intra-domain multicast-based mobility architecture, where a visiting mobile is assigned a multicast address to use while moving within a domain. Efficient handover is achieved using standard multicast join/prune mechanisms.Two approaches are proposed and contrasted. The first introduces the concept of proxy-based mobility, while the other uses algorithmic mapping to obtain the multicast address of visiting mobiles. We show that the algorithmic mapping approach has several advantages over the proxy approach, and provide mechanisms to support it.Simulations used to evaluate our scheme and compare it to other micro-mobility schemes - CIP and HAWAII. The proactive handover results show that both M&M and CIP show low handoff delay and packet reordering depth as compared to HAWAII. The reason for M&M's comparable performance with CIP is that both use bi-cast in proactive handover. M&M, however, handles multiple border routers in a domain, where CIP fails. Also using a proactive path setup mechanism, we show that M&M clearly outperforms CIP in case of reactive handover.